Iatrogenic T-Cell Lymphoma with Associated Hemophagocytic Lymphohistiocyotsis in a Patient with Long-Standing Rheumatoid Arthritis - X. A. Andrade; H. E. Fuentes; D. M. Oramas; H. Mann; P. Kovarik (Case Reports in Hematology)
Patients with rheumatoid arthritis are at increased risk of hematological malignancies, especially when exposed to immunosuppressive therapy. The mechanisms of lymphomagenesis remain poorly understood but factors implicated include high disease activity, exposure to antitumoral necrosis factor medications, and Epstein–Barr virus infection. Lymphoid malignancies of T-cell origin are uncommon in patients with rheumatoid arthirits. Clinical presentation with associated hemophagocytic lymphohistiocyotsis is rare and confers a poor prognosis. This case report illustrates a case of a patient with long-standing rheumatoid arthritis and an iatrogenic peripheral T-cell lymphoma with secondary hemophagocytic lymphohistiocytosis who achieved a complete response after intensive chemotherapy.